Lipid management in rheumatoid arthritis: a position paper of the Working Group on Cardiovascular Pharmacotherapy of the European Society of Cardiology. Issue 2 (9th August 2019) - Hollan, Ivana; Ronda, Nicoletta; Dessein, Patrick; Agewall, Stefan; Karpouzas, George; Tamargo, Juan; Niessner, Alexander; Savarese, Gianluigi; Rosano, Giuseppe; Kaski, Juan Carlos; Wassmann, Sven; Meroni, Pier Luigi
Abstract: Rheumatoid arthritis (RA) is associated with increased cardiovascular morbidity, partly due to alterations in lipoprotein quantity, quality and cell cholesterol trafficking. Although cardiovascular disease significantly contributes to mortality excess in RA, cardiovascular prevention has been largely insufficient. Because of limited evidence, optimal strategies for lipid management (LM) in RA have not been determined yet, and recommendations are largely based on expert opinions. In this position paper, we describe abnormalities in lipid metabolism and introduce a new algorithm for estimation of cardiovascular risk (CVR) and LM in RA. The algorithm stratifies patients according to RA-related factors impacting CVR (such as RA activity and severity and medication). We propose strategies for monitoring of lipid parameters and treatment of dyslipidaemia in RA (including lifestyle, statins and other lipid-modifying therapies, and disease modifying antirheumatic drugs). These opinion-based recommendations are meant to facilitate LM in RA until more evidence is available.